Node-RED dan Robotik pada Sistem Penyiraman Otomatis berbasis IoT - Wahyu Kurnia Dewanto; Aji seto Arifianto; Hariyono Rakhmad; Hermawan Arief Putranto; Muhammad Hafidh Firmansyah (Jurnal Teknologi Informasi dan Multimedia, 2024)
The Internet of Things (IoT) technology offers great potential in the agricultural sector, especially in the automation of plant irrigation systems. Many farmers face challenges with water use efficiency and real-time land condition monitoring. Manual irrigation systems often lead to water wastage. Currently, many centralized irrigation systems use a one-by-one watering approach, requiring multiple sensors to monitor each plant's condition, making them less efficient. To address this issue, this research developed an automated irrigation system controlled by Node-RED and robotic technology. The system is designed to require only one sensor to monitor the entire agricultural area, while still efficiently distributing water to many plants. Node-RED manages data from soil moisture and environmental temperature sensors, then activates the watering robot to distribute water according to the plants' needs. The system was tested by comparing manual and automatic methods using polybags. The soil moisture sensor sends data to Node-RED, which activates the watering robot when soil moisture falls below a set threshold. Test results show that the automated system can save up to 20% of water usage compared to manual methods, while keeping soil moisture within the optimal range. This system also enables real-time monitoring and control, providing a more efficient, timely, and resource-saving solution.